2013
DOI: 10.7750/biodiscovery.2013.10.1
|View full text |Cite
|
Sign up to set email alerts
|

From Roscovitine to CYC202 to Seliciclib – from bench to bedside: discovery and development

Abstract: This monograph reviews the discovery and development of the cyclindependent kinase inhibitor roscovitine (R-roscovitine, CYC202, Seliciclib). The authors summarise the in vitro and in vivo data that have formed the basis for clinical investigation of Seliciclib as an anti-cancer drug. Kinase selectivity, cellular effects and the pharmacological properties of the drug are discussed in addition to the clinical results of Seliciclib being reviewed. Novel results on the effect of the drug in cardiac hypertrophy ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 240 publications
(241 reference statements)
0
20
0
Order By: Relevance
“…The use of Roscovitine, a drug known to inhibit CDK-related activity in tumour cells, has demonstrated positive results in the prevention of cardiac hypertrophy [24][25][26][27]. The results suggest that cardiac hypertrophy is accompanied by activation of CDK9, and that target based inhibitors of the kinase pathway may be suitable molecular targets for therapeutic intervention in HCM.…”
Section: Current Applications Of Human Pluripotent Stem Cells In Drugmentioning
confidence: 99%
“…The use of Roscovitine, a drug known to inhibit CDK-related activity in tumour cells, has demonstrated positive results in the prevention of cardiac hypertrophy [24][25][26][27]. The results suggest that cardiac hypertrophy is accompanied by activation of CDK9, and that target based inhibitors of the kinase pathway may be suitable molecular targets for therapeutic intervention in HCM.…”
Section: Current Applications Of Human Pluripotent Stem Cells In Drugmentioning
confidence: 99%
“…It also contains four carbon aliphatic side chains. [ 23 ] 1,2,3‐Triazole‐cyanopyrimidine hybrids ( 1 ) reported by Li‐Ying et al, [ 24 ] replace “–NH” group at position‐2 of pyrimidine ring with isosteric sulfur‐bearing methylene linkage to evaluate their anticancer activity. Ma et al [ 25 ] reported methylene‐bearing sulfur‐containing cyanopyrimidine–thiourea hybrids ( 2 ) for their anticancer activity.…”
Section: Introductionmentioning
confidence: 99%
“…Further literature survey indicated that the presence of “–NH” or “–N” at position ortho to the cyano group alters the activity considerably. [ 23–26 ] Therefore, compounds bearing such patterns were also synthesized and evaluated for their anticancer activity and anti‐inflammatory potential. To study the biological target, compounds with good activity were also evaluated for their COX‐2 inhibition study.…”
Section: Introductionmentioning
confidence: 99%
“…Stem cells have many uses in the treatment of various diseases such as spinal cord injury, hormonal impairment, various types of syndrome, infertility, chronic hepatitis, pancreatitis, diabetes mellitus, and ischemic heart diseases such as congestive heart failure, etc. ( 10 ). Different types of therapies for heart failure are subject to some limitations; for example, in many studies, inappropriate drug therapy is reported as the most common cause of exacerbating heart failure ( 11 ).…”
Section: Introductionmentioning
confidence: 99%